Investigation of the Impact Strength of MC Blue Material Due to Temperature Variations - Yusuf Rahmansyah Siahaan, Muhammad; Rakhmad Arief Siregar; Faisal Amri Tanjung; Ahmad Yunus Nasution (DINAMIS, 2024)
Researchers carried out experimental testing on the MC Blue material using the charphy impact method. The MC Blue specimen was developed in a local workshop in Medan City, North Sumatra for three variations of testing temperature, namely normal temperature 31 oC, temperature 50 oC, and temperature 100 oC. The aim of this research is to determine the impact energy and impact strength values ​​of MC Blue material due to dynamic loads. The results of test data analysis show the mechanical characteristics of impact resistance with the highest value occurring in specimens at a temperature of 100 oC of 56.696 Joules at an average impact energy and an average impact strength value of 0.438 J/mm2. Meanwhile, the lowest Charphy impact resistance was shown by the normal temperature model of 31 oC of 17.975 Joules for the average impact energy value and the average impact strength value was 0.139 J/mm2. Temperature variations have a concrete impact, there is an increase in impact energy on the MC Blue material with a linear gradient equation y = 19.361x + 2.1467 and the impact strength value experiences a relevant increase due to temperature differences with a linear gradient equation y = 0.1495x + 0.0163.